If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3X + 7 = -2X + 4 Reorder the terms: 7 + -3X = -2X + 4 Reorder the terms: 7 + -3X = 4 + -2X Solving 7 + -3X = 4 + -2X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2X' to each side of the equation. 7 + -3X + 2X = 4 + -2X + 2X Combine like terms: -3X + 2X = -1X 7 + -1X = 4 + -2X + 2X Combine like terms: -2X + 2X = 0 7 + -1X = 4 + 0 7 + -1X = 4 Add '-7' to each side of the equation. 7 + -7 + -1X = 4 + -7 Combine like terms: 7 + -7 = 0 0 + -1X = 4 + -7 -1X = 4 + -7 Combine like terms: 4 + -7 = -3 -1X = -3 Divide each side by '-1'. X = 3 Simplifying X = 3
| 3/8*x=21/2 | | 4g+3=1g | | 3-2x=1000x | | 37w^2-312w-192924=0 | | (82.4-52)3/5=x | | -5X+13=-3X+7 | | (84.4-52)3/5=x | | z+72=8 | | 21X-39=13X-23 | | -11X-85=-6X-45 | | 6X-43=3X-22 | | 12X+134=6X+80 | | 3ln(x)+8=ln(3x)+12 | | 4psquared-12p+7=0 | | 45logx=3 | | 10X+36=6X+20 | | 34-9k=88 | | -5X-40=-3X-26 | | 2x^2-25x+80=0 | | -(3w+4)+5(w-2)-3(6w-8)=1 | | (x+35)=(3x+5) | | 10x^2+9x-117=0 | | 3x+8=4x-10 | | 10x^2+9x-108=0 | | -2x^2+54x=0 | | 6(y-6)/10(y-6) | | H(5x)=3x^2+2 | | 2x^2+52x=0 | | 25x+16y=287.28 | | 2x^2+18x+162=0 | | -2(2x-4x)=6+18 | | 4=2k+22 |